The Investment Strategy of Taiwan Futures Market after Quantitative Easing Monetary Policy - Lan, Yu-Wei; Lin, Dan; Lin, Lu (Archives of Business Research, 2017)
After the financial crisis in 2008, US Federal Reserve adopted quantitative easing monetary policy to boost the US economy. However, the hot money made tremendous shocks in financial markets. After 2015, the US job market stabilized and the Fed ended the QE and started raising interest rates. The aim of this study is to show that institutional investors affect TAIEX futures through MSCI Taiwan Index Futures, and consequently affect Taiwan 50 ETF. This study incorporates the price spread of TAIEX futures and MSCI Taiwan Index Futures in the model to conduct backtesting using program trading. This can help us determine if the mean reversion model is better than the contrarian model and the momentum model. The results show that the mean reversion model has higher profits and stabilities than the contrarian and momentum models. The results suggest that incorporating the price spread of TAIEX futures and MSCI Taiwan Index Futures and utilizing the mean reversion property of behavioral finance can enhance trading performance.